Implementasi Nilai-Nilai Budaya Organisasi Melalui Sosialisasi Budaya Organisasi - Dwi Irawati . (Universitas Kristen Maranatha, 2009)
This article decribes the significant impatcs of promoting corporate culture for employees, especially new recruits, in their understanding of corporate culture or corporate values. Promoting corporate culture and/or corporate values is often used by many organizations to help its employee recognize the organization's condition and surroundings. The success of this process depends on the role of the manager as well as the employee's involvement in achieving